2014
DOI: 10.5539/ijbm.v9n2p276
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Governance Matter in Meeting and Beating Analysts’ Forecasts

Abstract: Meeting and beating analysts' forecast has received substantial attention, most of studies investigate two principles problems: the valuation and value relevance of meeting and tools used to achieve benchmarks. This research is different, we investigate whether internal corporate governance impacts on meeting and beating analysts' forecasts and consistently do it, we also examine if these attributes alleviate opportunistic behavior.This paper contributes to the growing literature on earnings benchmarks, it tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…One of the most important governance mechanisms is board size as it indicates the participation of a board in company affairs and activities. The number of members on the board indicates the effectiveness in controlling and directing the company (Maztoul, 2014). Florackis (2008) claimed that small board size is likely to be better for coordination and communication.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…One of the most important governance mechanisms is board size as it indicates the participation of a board in company affairs and activities. The number of members on the board indicates the effectiveness in controlling and directing the company (Maztoul, 2014). Florackis (2008) claimed that small board size is likely to be better for coordination and communication.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…One of the most important governance mechanisms is the size of the board, as indicated by the board's participation in the company's interests and activities. The number of members on the board indicates effectiveness in controlling and directing the company (Maztoul, 2014). However, the research by Palaniappan (2017) revealed that the size of the board included in corporate governance has a negative relationship with the company's financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%